AB0205 Apoptotic cells induce B cell IL-10, and this is impaired in SLE. (23rd January 2014) - Heaney, J.; Amft, N.; Gray, M.
Abstract : Background: Apoptotic cells (ACs) induce murine B cells to produce IL-10 and in this way inhibit collagen-induced arthritis [1]. This led us to question whether regulatory B cells also play a role in the classical autoimmune disease SLE. Objectives: We aimed to demonstrated a role for AC in the induction of regulatory B cells in SLE. Methods: 14 healthy donors and 14 SLE patients volunteered for the study. Prior ethical approval was granted. Written consent was obtained. Venous blood was collected. B cells were isolated by density gradients and magnetic bead sorts or flow sorts. These were then incubated with pre-prepared apoptotic cells and 10ng/ml IL-4. These were then cultured for 72 hours at 37°C with 5% CO2 . Supernatants were harvested and tested for IL-10 by sandwich ELISA. Results: Healthy human B cells produced significantly more IL-10 (3.27 fold, p<0.004) when co-cultured with ACs than B cells, or ACs alone. Flow sorted memory, marginal zone B (MZB) cells and naive B cells were cultured with ACs. Memory and MZB cells produced significantly more IL-10 than naive B cells. B cell IL-10 induction by ACs was significantly lower in SLE patients with high anti-dsDNA titres (p<0.0031), and there was an inverse logarithmic relationship between anti-dsDNA titre and B cell IL-10 production (p<0.0011). There was a trend towards a significantly higher level of AC induced B cell IL-10 in patients with quiescent disease compared to active disease (P<0.28), and a weak inverse relationship between ESR and B cell IL-10 production (p<0.312). Conclusions: Others have shown that the rate of apoptosis may be increased in SLE [2], however an increased rate of phagocytosis has also been demonstrated in the condition [3]. These events may be related and not be directly causing autoimmunity. Indeed high apoptosis rates are ordinarily found in organs such as the thymus without the development of autoimmunity. The current data suggests that a defect in the appropriate immunoregulatory recognition of apoptotic cells in SLE may be an alternative explanation of the evolution of this condition. We have recently published evidence to support this in both murine and human models. We have demonstrated that CD27 + B cells are the sub-population most able to produce IL-10 in response to apoptotic cells [4]. The kinetics of this has yet to be confirmed. It may be that the generation of apoptotic cells acts as a natural immunosuppressant to dampen exaggerated immune responses, with MZB cell dampening innate responses, and memory cells dampening adaptive responses. References: Gray M, et al. Apoptotic cells protect mice from autoimmune inflammation by the induction of regulatory B cells. Proc. Natl. Acad. Sci. U. S. A. 2007;104:14080-14085. Emlen W, et al. Accelerated in vitro apoptosis of lymphocytes from patients with systemic lupus erythematosis. Journal of Immunology 1994; 152:3685-3692. Sarmiento L, et al. Opsonization by anti-dsDNA antibodies of apoptotic cells in systemic lupus erythematosis. Autoimmunity 2007; 40:337-339. Miles K, et al. A tolerogenic role for Toll-like receptor 9 is revealed by B-cell interaction with DNA complexes expressed on apoptotic cells. Proc. Natl. Acad. Sci. U. S. A. 2012; 109:887-892. Disclosure of Interest: None Declared